The Dean : A Biography of A. A. Potter - Eckles, Robert B. (Book collections on Project MUSE., 2022)
More than 20,000 engineering students at Purdue University have been touched in some way by the ides or the warm personality of Andrey A. Potter, who served for 33 years as dean of the Schools of Engineering at Purdue, the world's largest engineering institution. Awarded the honorary title of "Dean of the Deans of Engineering Universities" in 1949 by his alma mater, MIT, Potter has been a teacher for 48 years and a dean for 40. Among his thousands of colleagues at Kansas State, Purdue, and the professional societies he has headed, he is known with respect and affection simply as "the Dean." This book, illustrated with photographs, traces his life from his boyhood in Russia and his journey at age 15 to America where, he contends, his life really began. We see him as a student cutting lab classes to attend an afternoon concert of the Boston Symphony, as a young man growing a van Dyke beard to make himself look older for his first job as an engineer with General Electric, and as a new assistant professor at Kansas State, courting his schoolteacher-sweetheart in a horse and buggy. His contributions to the engineering profession are many. He was president of the leading professional societies, prepared an exhaustive state-of-the-art study of engineering, and enhanced the public service aspects of his field by participating in government advisory boards. Greatly admired for his work with the National Patent Planning Commission, where he protected the right of the inventor to the fruits of his ingenuity, he is also respected for his publications in his own area of research, power generation and super-critical steam. A selected bibliography lists his writings. At Kansas State and Purdue, he organized curricula to emphasize study that could be used by engineers to solve problems in agriculture and industry; this brought farmers and businessmen closer to the campus and more aware of the university's service to their state. He found deepest pleasure, however, not in these accomplishments, but in the personal contacts he established with students and colleagues. In his own words, "the secret of success is to love one's fellow men."